Ultra-High-Pressure Hydraulic Slitting Pressure Relief and Penetration Enhancement Technology and Equipment for Soft Coal Seams. (16th July 2022) - Niu, Xingang; Zhao, Yi; Li, Ke; Zhang, Yongjiang
Abstract : There is a "bottleneck effect" in the extraction process of ordinary boreholes. It is crucial to enhance the permeability of the boreholes. In this paper, a set of ultra-high-pressure water jet-based drilling and slotting integrated equipment was designed and applied, and the ultra-high-pressure safeguarding technology of several key components has been studied. Finally, the gas drainage effect of slotted boreholes and ordinary boreholes was investigated through field tests. The test results showed that after using ultra-high-pressure hydraulic slotting, the average drainage concentration of slotted boreholes is 1.49 times that of the ordinary boreholes. The average extraction scalar volume of slotted drilling is 3.02 times that of ordinary boreholes. Under the condition of original content of 12 m 3 /t, the extraction radii of slotted boreholes in 3 months and 6 months are 3.76 m and 4.76 m, respectively. The effective radius of the slotted boreholes is 1.76 times that of the ordinary boreholes, which indicate that the ultra-high-pressure hydraulic slotting technology can effectively relieve the pressure and increase the permeability of the soft coal seam.